Sodobne metode rehabilitacije govora po laringektomiji - Obolnar, Nika (Rehabilitacija (Ljubljana), 2018)
The main goal of rehabilitation after laryngectomy, which is a surgical procedure for a laryngeal and hypopharyngeal cancer treatment, is to establish the production of a voice which consequently restores the patient's ability to speak. Here we focus on different options for voice rehabilitation. Its objective is to achieve the airflow and consequent vibration within the upper alimentary tract. There are three main contemporary methods - esophageal speech, electrolarynx and insertion of speech prosthesis to allow tracheo-esophageal speech. In Slovenia, esophageal speech is the method of rehabilitation used most often, whereas in Western countries the use of speech prosthesis is the most common.
Keywords: electrolarynx; elektrolarinks; esophageal speech; ezofagealni govor; govorne proteze; laringektomija; laryngectomy; rehabilitacija govora; rehabilitation of speech; Rehabilitation of Speech and Language Disorders; voice prostheses